Atypical Actinobacillus pleuropneumoniae serotype 12 strains with a higher virulence potential - Antony T. Vincent; Sonia Lacouture; Guillaume St-Jean; Rodrigo Tapia; Servane Payen; Michiha Kon; Joachim Frey; Ho To; Marcelo Gottschalk (Veterinary Research)
Abstract Actinobacillus pleuropneumoniae is the causative agent of porcine pleuropneumonia, a disease of major economic impact. Serotype 12 is generally considered to be of low virulence and is typically associated with subclinical infections. However, we describe four atypical serotype 12 field strains recovered from severe clinical outbreaks in Chile. These strains exhibited an unusual toxin gene profile (apxIICA, apxIIICA, apxIBD, apxIIIBD), suggesting the ability to produce both ApxII and ApxIII toxins. Comparative genomic analyses revealed that these atypical strains carry the capsule genes of serotype 12 but the LPS biosynthesis genes of serotype 15, indicating a hybrid genomic structure. Phylogenetic analysis confirmed that they cluster separately from classical serotype 12 strains and are closely related to other atypical strains from Japan, USA, and Canada. Experimental infection in pigs demonstrated significantly increased virulence of the atypical Chilean strain compared to the reference strain of serotype 12, with higher clinical scores, severe lung lesions, and atypical serological responses against serotypes 3/6/8/15/17. These findings challenge the traditional view of serotype 12 as low-virulence and highlight the need for improved diagnostic approaches that incorporate both capsule and LPS profiling. The existence of these atypical strains has important implications for disease surveillance, diagnostics, and vaccine development in swine health management.